2013
DOI: 10.1111/josh.12000
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Pilot School Snack Programs on Milk and Alternatives Intake in 2 Remote First Nation Communities in Northern Ontario, Canada

Abstract: These illustrations show the potential of snack programs to address the low intakes of milk and alternatives among youth in remote FNs. Community-level constraints must be addressed for sustained program benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 105 interventions reviewed, 21% or 20% of all interventions, conducted follow‐up analysis (Table ). Six conducted a midterm‐ only analysis, 12 conducted a long‐term‐only analysis, and 3 conducted both a midterm and long‐term analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Each ISR community has active school-based meal and snack programs that both improve access to healthful food (theme 1) and help build nutritional knowledge and skills (themes 2 and 7). School-based food programs have had demonstrable benefits on food and nutrient intake among Indigenous youth in remote northern Ontario (Gates, Hanning, Gates, Stephen, & Tsuji, 2016;M. Gates, Hanning, Gates, McCarthy & Tsuji, 2013;Skinner, Hanning, Metatawabin, Martin, & Tsuji, 2012); however, their impact among Inuit youth has not been reported.…”
Section: Nutrition Education and Food Preparation Programsmentioning
confidence: 99%
“…The Mission was somewhat successful in producing diverse foods within a challenging environment and short growing season, but their departure and subsequent closing of residential schools in the late 20th century ended local agricultural production and left remote First Nations dependent on an unreliable, import-based food system [2]. Modern food systems in these remote First Nations often lack nutritional quality [3][4][5][6], bear high transportation costs, and perpetuate the loss of traditional Aboriginal food systems and associated knowledge [7], ultimately impacting individual and community health [8]. This import-based system is also extremely resource-intensive, while it simultaneously perpetuates reliance on the unstable fossil-fuel industry and global food economy [9,10].…”
Section: Food Security In Sub-arctic First Nationsmentioning
confidence: 99%